2016
DOI: 10.1038/srep23642
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and functional characterization of glycosylation-associated mutational landscapes in colon cancer

Abstract: The molecular basis of aberrant protein glycosylation, a pathological alteration widespread in colorectal cancers (CRC), and the mechanisms by which it contributes to tumor progression remain largely unknown. We performed targeted re-sequencing of 430 glycosylation-associated genes in a series of patient-derived CRC cell lines (N = 31) and matched primary tumor tissues, identifying 12 new significantly mutated glycosylation-associated genes in colon cancer. In particular, we observed an enrichment of mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 54 publications
1
42
0
Order By: Relevance
“…In particular, our previous studies in familial and sporadic colorectal cancers (CRCs) identified functionally-inactivating germline and somatic mutations in the gene encoding for GALNT12 (Polypeptide N-acetylgalactosaminyltransferase 12) [7], suggesting that aberrant glycosylation in cancers could stem from genetic defects in the glycosyltransferase genes. These findings prompted us to undertake an in-depth characterization of CRC-associated mutational alterations in genes encoding glycosylation enzymes using targeted next-generation sequencing [8]. Of the 430 glycosylation-associated genes assessed, 36 genes exhibited mutational alterations (missense, nonsense, splice site and frameshift mutations) in colorectal cancers, with 12 genes displaying significantly higher mutation rates than the expected background rate in CRCs [8].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, our previous studies in familial and sporadic colorectal cancers (CRCs) identified functionally-inactivating germline and somatic mutations in the gene encoding for GALNT12 (Polypeptide N-acetylgalactosaminyltransferase 12) [7], suggesting that aberrant glycosylation in cancers could stem from genetic defects in the glycosyltransferase genes. These findings prompted us to undertake an in-depth characterization of CRC-associated mutational alterations in genes encoding glycosylation enzymes using targeted next-generation sequencing [8]. Of the 430 glycosylation-associated genes assessed, 36 genes exhibited mutational alterations (missense, nonsense, splice site and frameshift mutations) in colorectal cancers, with 12 genes displaying significantly higher mutation rates than the expected background rate in CRCs [8].…”
mentioning
confidence: 99%
“…These findings prompted us to undertake an in-depth characterization of CRC-associated mutational alterations in genes encoding glycosylation enzymes using targeted next-generation sequencing [8]. Of the 430 glycosylation-associated genes assessed, 36 genes exhibited mutational alterations (missense, nonsense, splice site and frameshift mutations) in colorectal cancers, with 12 genes displaying significantly higher mutation rates than the expected background rate in CRCs [8]. Interestingly, further enrichment analysis of the 12 genes showed that three genes, B3GNT2 (β-1,3-N Acetylglucosaminyltransferase 2), B4GALT2 (β-1,4-Galactosyltransferase 2) and ST6GALNAC2 (α-N-Acetylgalactosaminidyl α-2,6-Sialyltransferase 2), belonged to polylactosamine and N- and O-glycosylation pathway [8].…”
mentioning
confidence: 99%
See 3 more Smart Citations